Measuring the impact of Socio-Economic Factors on school’s Technical Efficiency - Stergiou, KONSTANTINOS; Tsakiridou, Helen (Archives of Business Research, 2019)
This paper investigates and evaluates the effectiveness and the Technical Efficiency of secondary education units in the region of Western Macedonia in Greece. Using Data Envelopment Analysis (DEA) at a first stage analysis school efficiency is measured in schools where multiple inputs produce multiple outputs. In this study the inputs chosen are: the teacher student ratio, the staff student ratio and the computer student ratio of each educational unit. The output (student performance) refers to the student’s achievement in the national exams during the school year of 2015 – 16. In the second stage analysis, efficiency scores from the first stage analysis, were explained in a regression with the environmental variables as independent variables. The independent variables chosen were divided in two categories: the variables from the direct school environment (school size, teacher’s experience, teacher’s qualifications and per student expenses) and variables from the wider school environment in (GDP per capita, unemployment rate and educational level of each school’s area). DEA showed that 4 out of the 29 educational units were characterized as technical efficient becoming benchmarks for all the others with lower efficiency. In the second stage, regression analysis shows that teachers’ experience significantly affects school efficiency while teacher’s qualifications, school size and per student expenses do not affect school efficiency. Concerning the variables from the wider social environment, GDP per capita, unemployment rate and educational level in each school’s area didn’t show a statistically significant effect on the technical efficiency of the educational units.